Sorevnovatel'nyj stress u predstavitelej razlicnych vidov sporta po pokazateljam variabel'nosti serdecnogo ritma - Agadzanjan, N. A.; Batocyrenova, T. E.; Semenov, Ju. N.; Kislicyn, A. N. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The article deals with the results of investigations of the competition stress of the athletes going in for different kinds of sport according to the indices of the heart rate variability (HRV). 94 participants of competitions of different levels going in for such sport games as volley-ball, mini-football, boxing, free wrestling, power-lifting, bullet shooting have been investigated. In order To analyze the heart rate variability APK "Varicard" and ISKIM-6 software have been used. The quantitative estimation of the stress level that the athletes have during competitions have been made in terms of indices of the heart rate variability. It has been shown that the changes of the vegetative regulation under the conditions of the competition stress have been characterized by the considerable reduction of the indices reflecting the activity of the parasympathetic part (pNN50, RMSSD, SDNN, HF%) and the activity increase of the sympathetic part (SI, AMo) of the vegetative nervous system. The direction and availability of dynamics of the indices changes of heart rate variability depend on kind of sport, type of vegetative regulation and class of athletes and the importance of competitions.